The Influence of Project-Based Learning Model on Creativity and Cognitive Learning Outcomes of the Students of SMAN 1 Amarasi Timur, Indonesia - Rosalinda Stheylani Sakbana; Widha Sunarno; Sri Budiawanti (GoAcademica Research & Publishing, 2021)
Creativity is one of four crucial competencies for students in the 21st century. It has an important role in forming a superior generation to face challenges 4.0. This research is set to determine the difference of the influence of using the project-based-learning model on the students' creativity and cognitive learning outcomes. It is experimental research by using non-parametric data analysis techniques. Kruskal Wallis test is employed to test hypothesis then a post hoc follow-up test (Mann-Whitney U) is carried out. The sample is the entire population of the students of class X SMAN 1 Amarasi Timur, Indonesia. Creativity and cognitive learning outcomes are measured by using material momentum and impulse. Student’s creativity is measured by using a closed questionnaire that consists of positive, negative statements, and project work results. Meanwhile students’ cognitive learning outcomes are measured using a multiple-choice test with 22 questions. The results research inform that there is a significant influence of using the project-based-learning model on students' creativity and cognitive learning outcomes.